Virtual cultural circle: promoting the health of nurses fighting the covid-19 - Jeane Barros de Souza; Carine Vendruscolo; Eleine Maestri; Júlia Valéria de Oliveira Vargas Bitencourt; Crhis Netto de Brum; Adriana Remião Luzardo (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To report a virtual Cultural Circle experience implemented with nurses to allow them to dialogue and promote health amidst the pandemic of the Coronavirus Disease 2019 (COVID-19). Method: Experience report of a virtual Cultural Circle based on Paulo Freire's framework. The stages were correlated to the oil lamp, the symbol of the nursing profession: the lamp body was considered the Thematic Investigation, the lamp support corresponded to Encoding and Decoding, and the light corresponded to Critical Unveiling. Fourteen nurses working in different health settings located in different Brazilian regions participated. Results: Two themes emerged: adjusting my inner light and taking care of my family and work. Final considerations: The nurses exchanged experiences and strengthened themselves to overcome the challenges imposed by the fight against the COVID-19, acquiring autonomy to take care of themselves and provide care to others.